A First Look at Internal Waves in the Great Barrier Reef Lagoon - George Marmorino (Remote Sensing, 2024)
The Great Barrier Reef lagoon is a large, relatively shallow area of the Australian continental shelf, isolated from the open ocean by a dense matrix of coral reefs. As the lagoon is generally vertically well mixed by strong tidal currents and wind, it is perhaps not surprising there is no mention in the open literature of the occurrence of internal waves there. Nevertheless, high-resolution satellite imagery is shown in this article to reveal the characteristic surface expressions of nonlinear internal waves in the lagoon. The waves are confined to periods of low winds in austral spring and summer, making them a potentially important mechanism for the dispersal of algae and planktonic larvae. The imagery suggests a link between the waves and tidally forced submesoscale jets and vortices, but the actual mechanism generating the internal waves is unclear and requires investigation.